2023
DOI: 10.1177/15579883231184078
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and Gender Minorities Inclusion and Uptake of Sexual and Reproductive Health Services: A Scoping Review of Literature

Methembe Yotamu Khozah,
Wilfred Njabulo Nunu

Abstract: Despite the efforts to ensure that sexual and reproductive health services are integrated into global, regional, and national initiatives, a significant number of countries are overwhelmed by frames of exclusion and violations of fundamental human rights, particularly for sexual and gender minority groups such as lesbians, gays, bisexuals, and transgender people. This study sought to review the literature on access and barriers faced by sexual and gender minorities. A scoping literature review was conducted on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Significant progress has been made in preventing new HIV infections, although HIV transmission among MSM remains challenging (UNAIDS, 2016a(UNAIDS, , 2016b. Many countries have laws prohibiting same-sex sexual relations, and Pérez-Jiménez et al (2009) noted that most interventions for people living with HIV have focused largely on heterosexuals in Latin America and Sub-Saharan Africa (Khozah & Nunu, 2023). There is a significant lack of programmatic intervention research to address self-management among this population.…”
Section: Introductionmentioning
confidence: 99%
“…Significant progress has been made in preventing new HIV infections, although HIV transmission among MSM remains challenging (UNAIDS, 2016a(UNAIDS, , 2016b. Many countries have laws prohibiting same-sex sexual relations, and Pérez-Jiménez et al (2009) noted that most interventions for people living with HIV have focused largely on heterosexuals in Latin America and Sub-Saharan Africa (Khozah & Nunu, 2023). There is a significant lack of programmatic intervention research to address self-management among this population.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported MSM preferring to access their PrEP from MSM-friendly facilities due to barriers they face in non-MSM facilities, such as negative attitudes from health care workers ( Adeagbo et al, 2021 ; Graham et al, 2022 ; Holloway et al, 2017 ; Patrick et al, 2019 ), lack of confidentiality by health care providers ( Graham et al, 2022 ), and PrEP being unaffordable ( Dean et al, 2023 ; Graham et al, 2022 ; Kota et al, 2021 ; Voglino et al, 2021 ). In Sub-Saharan African countries where same-sex sexual interaction is criminalized, health service providers also exhibit negative attitudes toward MSM, thus reducing their ability to access services they need, such as accessing PrEP ( Khozah & Nunu, 2023 ; Munyimani & Nunu, 2022 ). Despite Zimbabwe criminalizing same-sex sexual interaction, health care providers must be educated and trained to render good quality services to MSM without any form of discrimination because transmission of HIV and AIDS remains unacceptably high among this population.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors hamper PrEP uptake for HIV prevention in African nations. Different authors have alluded to this low uptake of PrEP among MSMs in different country contexts in Sub-Saharan Africa to be a lack of awareness and knowledge ( Matacotta et al, 2020 ), stigma and discrimination ( Isano et al, 2020 ; Keuroghlian et al, 2021 ), legal and policy barriers ( Embleton et al, 2023 ; Mbilizi Chimwaza et al, 2022 ), limited access to health care ( Mgodi et al, 2023 ; Muraguri et al, 2012 ), cost and affordability of health services ( Mgodi et al, 2023 ), health care provider bias and inadequate training ( Keuroghlian et al, 2021 ), and lack of tailored health services and privacy and confidentiality concerns ( Khozah & Nunu, 2023 ; Munyimani & Nunu, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation